Antibacterial activity of ethanol extract of banana, cassava, and pineapple peels against a fish pathogen Aeromonas hydrophila - DINI SISWANI MULIA; RAIH RAICHA; CITRA PUSPANING LUNGGANI; SISKA NUR ERINA; JULI ROCHMIJATI WULIANDARI; CAHYONO PURBOMARTONO; ALIM ISNANSETYO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Mulia DS, Raicha R, Lunggani CP, Erina SN, Wuliandari JR, Purbomartono C, Isnansetyo A. 2023. Antibacterial activity of ethanol extract of banana, cassava, and pineapple peels against a fish pathogen Aeromonas hydrophila. Biodiversitas 24: 481-485. Aeromonas hydrophila is the most virulent bacteria for almost all freshwater fish species. One method to control pathogenic bacteria in fish should be safe and environmentally friendly, including utilizing natural wastes such as banana peels (Musa paradisiaca), cassava peels (Manihot esculenta), and pineapple peels (Ananas comosus). These natural wastes contain bioactive compounds. Their utilization increases the waste value. This study aims to determine the potential of banana peel, cassava peel, and pineapple peel waste as an antibacterial against A. hydrophila, a causing agent of Motile Aeromonas Septicemia (MAS) in freshwater fish. Parameters observed included phytochemical compounds, MIC, and MBC values of banana, cassava, and pineapple peels. Phytochemical screening was performed using thin-layer chromatography (TLC) and foam test. The microdilution method carried out the antibacterial activity of banana peel, cassava peel, and pineapple peel against A. hydrophila. It determines the minimum inhibitory concentration (MIC); and the minimum bactericidal concentration (MBC) values. Phytochemical screening results showed that banana, cassava, and pineapple peel extracts contained flavonoids, alkaloids, terpenoids, tannins, and saponins. The MIC values of banana peel, cassava peel, and pineapple peel extract were 600, 400, and 200 µg/mL, respectively. The MBC values of banana peel, cassava peel, and pineapple peels were 4 × MIC, 2 × MIC, and 1 × MIC, respectively. Extract of pineapple peel exhibited better antibacterial activity than banana and cassava peels. However, the three waste extracts indicated the antibacterial potential to be developed as natural bactericides to control A. hydrophila bacterial disease.